Kilimin Ekfrasis ve Göstergelerarasılık Bağlamında Kullanımı: Ayla Çınaroğlu'nun Sihirli Kilim'i. - Demiral, Bayram (Yedi)
The arts are classified by aesthetic theorists into two main groups, verbal and non-verbal. Various exchanges can take place between and among these branches of art. The exchanges between verbal arts are defined as intertextual relations. The exchanges between non-verbal arts and verbal arts are described as Intersemiotic relations. Ekphrasis, which is one of the intersemiotic relations, is defined as the inclusion of a non-verbal art in verbal art or the representation of nonverbal arts in verbal arts. In Ayla Çınaroğlu's fairy tale book called Sihirli Kilim, that employs one of the traditional weaving types, is used as the basic element of the fiction. In this study, which aims to determine the transformations of rugs and their motifs in a fairy tale text, the method of analysis intersemiotic was used. In this study, linguistic and visual transformations of rugs and motifs are analyzed in the context of intersemiotic relations and ekphrasis. In the text of the tale, rugs and their motifs, which can be considered non-verbal arts, are included in the verbal art, at which point ekphrasis appears. In the linguistic context, the ram's horn motif turns into a ram, the wolf's track motif turns into a wolf, and the waterway motif turns into a stream. This situation can be evaluated as the reproduction of the rug motif in the linguistic field. While the rug and its motifs are transferred to the context of the book as an Illustration, the qualities of the weaving and motifs such as material, location, and shape are transformed. The visuals of the motifs in the book remind the reader that the linguistic indicators created by referring to the motifs in the text are derived from the rug motifs and that the narrative is constructed from the rug surface. As a result, rugs and their motifs have been used in the text, both in meaning and form. The linguistic and visual inclusion of rugs and their motifs in the book ensures the circulation, recognition, and dynamism of traditional weaving in other contexts. In addition, the book enables children to acquire visual and linguistic information about rugs and motifs, which are material cultural elements.